Analisis Pergeseran Pertumbuhan Struktur Ekonomi dan Sektor Unggulan Kota Bandung - Nazmi Aulia Robbani; Ade Yunita Mafruhat (Bandung Conference Series: Economics Studies, 2023)
Abstract. The city of Bandung is one of the largest metropolitan cities in West Java Province, apart from that the city of Bandung has quite large industrial and business areas, therefore the city of Bandung has a trade in goods and services sector which has an important role in economic growth which creates a leading sector. This study aims to analyze the structure of economic growth and economic excellence in the city of Bandung by using the Location Quotient (LQ) and Shift Share Methods. The data analyzed is data from GRDP in Bandung City based on constant prices according to business field data. The results of the analysis show that the city of Bandung has experienced an increase in economic growth every year because of the factors that encourage this growth. The city of Bandung has leading and non-leading sectors. The sectors that are becoming less prominent in the city of Bandung are the mining and quarrying sector as well as electricity procurement. Abstrak Kota Bandung termasuk Kota Metropolitan terbesar di Provinsi Jawa Barat, selain itu Kota Bandung memiliki kawasan industri dan bisnis yang cukup besar, oleh karena itu Kota Bandung memiliki sektor perdagangan barang dan jasa yang memiliki peran penting dalam pertumbuhan ekonomi yang menciptakan sektor unggulan. Penelitian ini bertujuan untuk menganalisi struktur pertumbuhan ekonomi dan keunggulan ekonomi di Kota Bandung dengan menggunakan Metode Location Quotient (LQ) dan Shift Share, data yang dianalisis adalah data dari PDRB Kota Bandung berdasarkan harga konstan menurut data lapangan usaha. Hasil analisis menunjukan bahwa Kota Bandung mengalami peningkatan dalam pertumbuhan ekonomi setiap tahunnya karena adanya faktor yang mendorong pertumbuhan tesebut. Kota Bandung memiliki sektor unggulan dan non unggulan. Sektor yang menjadi kurang unggul dikota bandung ini ialah sektor pertambangan dan penggalian serta pengadaan listrik.